Ultrafine PdOx nanoparticles on spinel oxides by galvanic displacement for catalytic combustion of methane. Issue 22 (22nd October 2019) - Zhang, Zeshu; Hu, Xuefeng; Zhang, Yibo; Sun, Liwei; Tian, Heyuan; Yang, Xiangguang
Abstract : The excellent catalytic activity of methane combustion over the Pd/NiCo2 O4 is attributed to ultrafine Pd nanopariticles and a tight Pd-spinel interface obtained by galvanic displacement. Abstract : High light-off temperature and poor water-tolerance at low temperature are the main drawbacks of catalysts for catalytic methane combustion. Herein, the galvanic displacement method was adopted to obtain ultrafine PdO x nanoparticles (∼1 nm) on NiCo2 O4 and build a tight Pd–NiCo2 O4 interface. As a comparison, additional reference samples were prepared by conventional synthetic methods. The synthesized catalysts were characterized by XRD, TEM, XPS, H2 -TPR, CH4 -TPR, CO2 -TPD and in situ DRIFT techniques. It is found that the catalyst obtained by galvanic displacement has more Pd 4+ and oxygen vacancies. The high oxidation state of Pd is more conducive to the activation of methane, and a large number of oxygen vacancies can promote the catalytic reaction rate. Thus, this catalyst displays outstanding catalytic activity with T 90 = 260 °C and excellent water-tolerance below 300 °C. In addition, a simple model was built based on the obtained results to understand the catalytic mechanism and provide a universal strategy for rational design of catalysts for low temperature complete oxidation of methane.